The Photochemical Isomerisation of Hexatomic Heterocyclic Compounds - D’Auria, Maurizio (Current Organic Chemistry, 2021)
The photochemical isomerisation of hexatomic heterocyclic compounds has been discussed. The attention was focused on the mono- and dinitrogen hexatomic heterocycles. To justify the photochemical isomerisation of pyridines, Dewar isomers, azaprismane, and azaprefulvene derivatives have been proposed. The photoisomerisation of pyridinium salts requires a ring reduction with the formation of arizines. Pyridinium ylides gave photoisomerisation reaction through the formation of the corresponding azirines, while pyridinium N-oxide was required to react for the formation of the corresponding oxaziridines. The photochemical isomerisation of pyrazine derivatives, Dewar isomers, diazaprismane, and benzvalene intermediates has been proposed to justify the observed reactivity. Finally, in the case of pyridazine and pyrimidine derivatives, Dewar isomers were used to explain the obtained reaction products. In the discussion of the results, the presence of different mechanistic hypotheses has been evidenced.
Keywords: quinoline